Leadership, strategy, and innovation in tourism and hospitality - Dias, Á. (Leadership in tourism and hospitality, 2025)
This study examines the configurational paths that lead to high and low innovation among tourism entrepreneurs. It investigates the interplay between leadership, community-centered strategies, place identity, and self-efficacy in shaping entrepreneurial innovation. By adopting a fuzzy-set qualitative comparative analysis (fsQCA) approach, this study identifies the different combinations of these factors that are associated with high and low levels of innovation. The findings reveal that there is no single, universally applicable formula for fostering innovation among tourism entrepreneurs. Instead, multiple configurations of leadership, community-centered strategies, place identity, and self-efficacy can lead to high levels of innovation. These findings have important implications for both entrepreneurs and policymakers seeking to promote innovation in the tourism industry.